Hydrodynamic and hydromagnetic stability of two superposed elastico - viscous fluids of different permeability with dust in porous medium - Singh, Mahinder; Mehta, C.B. (Zielona Góra: Uniwersytet Zielonogórski)
Rayleigh-Taylor instability of two superposed Walters? B has elastico-viscous fluids in a uniform magnetic field through a porous medium with different permeability been studied to include the suspended (dust) particles effect. Using normal mode technique a dispersion relation has been derived. The stability analysis has been carried out. The magnetic field stabilizes the unstable configuration for the wave number band K>K* in which the system is unstable in the absence of the magnetic field. It is also found that for a potential stable arrangement for Walters B? elastico-viscous fluids of different permeabilities in the presence of suspended particles through a porous medium the system is stable, whereas in the potentially unstable case instability of the system occurs.
Keywords: Rayleigh-Taylor instability; magnetic filed; suspended particles; Walters` B fluid; different permeability; porous medium